SCIENTIFIC, TECHNOLOGICAL AND ORGANIZATIONAL DECISIONS TO INCREASE EFFICIENCY AND TIMELINESS OF HEART TRANSPLANTATION - S. V. Gautier (Vestnik Transplantologii i Iskusstvennyh Organov, 2014)
Aim. To analyze approaches to pretransplant treatment of potential heart recipients and heart donation criteria, directed to reduction of mortality on a waiting list and to increase of volume and effi ciency of heart transplantations.Methods and results. Data on 285 HT recipients (performed in 2008–2013) were analyzed. The analysis and comparison of patients with circulatory support before heart transplantation, using «high-risk» donors (aged over 40 years, with left ventricular hypertrophy ≥ 1.5 cm, after cardiopulmonary resuscitation, with the reduced systolic function of the left ventricle (< 40%), with potentially repair pathology of the heart valve and coronary arteries); to high risk recipients (over 60 years, with high pulmonary hypertension and earlier operated) were made.Conclusion. The proposed scientifi c, technological and organizational solutions made possible the timely performance of heart transplantation to patients with an inevitable lethal outcome as a result of heart failure.